2008
DOI: 10.1007/s00163-007-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Activity modelling in a collaborative ceramic tile design chain: an enhanced IDEF0 approach

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In our study we observed the presence of different actors and different kinds of relationships among them [8]. We named these actors "stakeholders", following the definition by Claros Salinas et al [14]: "a person who is involved in the design.…”
Section: Stimulators and Stimuli Frameworkmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study we observed the presence of different actors and different kinds of relationships among them [8]. We named these actors "stakeholders", following the definition by Claros Salinas et al [14]: "a person who is involved in the design.…”
Section: Stimulators and Stimuli Frameworkmentioning
confidence: 81%
“…Finally, the representation of the activity model for the desired state ("should-be" model) was tackled directly with an "improved" IDEF0, (IDEF0+) [8].…”
Section: Figure 1 Ideation Process Modelled In Idef0 (Cedam)mentioning
confidence: 99%
“…Identifying dependency loops that remain and finding ways to eliminate them, for instance by splitting some tasks into several parts, allows the project to be sequenced and a schedule to be produced (Austin et al 2000). More recently, Romero et al (2008) introduce an enhanced IDEF0? approach.…”
Section: Task Dependency Modelsmentioning
confidence: 99%
“…Explicit descriptions of should-be and to-be activities and processes are key elements in implementing industrial projects (Romero et al 2008). For instance, in the automotive industry, the purpose of project decomposition into documented deliverables is to provide a vehicle that meets the expectations of the customer.…”
Section: Introductionmentioning
confidence: 99%